El involucramiento parental y el desarrollo de la determinación en los estudiantes colombianos de bajos recursos (2020)
¿How does the agency influence the processes of transmission of cultural capital? The classical theories on the subject have not given much relevance to this question. Thus,this article investigates what factors explain the agency of a sample of 1,487 low-income Colombian students, outstanding academically, and those who presented the Saber 11 tests in mid-2015. By means of a linear regression analysis it was found that, controlled for several psychological and demographic factors, parental involvement is essential to explain higher levels of student agency behaviors. This demostrates how struggling students can achieve success despite the problems. Likewise, it provides new empirical directions to the studies on social class reproduction, which had focused on the advantages that the upbringing of the upper classes supposes, but not in the virtues of the upbringing of the lower classes.